Civic engagement and mental health trajectories in Norwegian youth - Wiium, Nora; Kristensen, Sara Madeleine; Årdal, Elisabeth; Bøe, Tormod; Gaspar de Matos, Margarida; Karhina, Kateryna; Larsen, Torill Marie Bogsnes; Urke, Helga Bjørnøy; Wold, Bente (Frontiers in Public Health, 2023)
Applying variable-centered analytical approaches, several studies have found an association between civic engagement and youth mental health. In the present study, we used a person-centered approach to explore whether civic engagement was related to optimal trajectories of mental health compared to other trajectories. We also examined how sociodemographic factors, such as socioeconomic status (SES), gender and age were related to youth mental health trajectories. Our sample comprised 675 students (aged 16-22) who had participated in three waves of data collection (Mage = 18.85, SD = .55; 43% males) in the COMPLETE project, a cluster-randomised controlled trial that involved Norwegian upper secondary schools. The results revealed three trajectories of mental health (reflecting a combination of mental distress and mental well-being): optimal, intermediate, and sub-optimal. Contrary to our expectations, higher levels of civic engagement were not related to the optimal trajectory of mental health versus other trajectories. However, we found that students who reported higher levels of SES and males were more likely to follow the optimal trajectory compared to other trajectories. While the findings on civic engagement could be due to our measurement’s inability to capture the concept of “dugnad”, a well-established civic activity in the Norwegian society, the findings regarding the influence of SES and gender suggest that there is still more work to be done concerning the assessment and advancement of factors that can address mental health inequalities across SES and gender.